2020
DOI: 10.3345/cep.2020.00850
|View full text |Cite
|
Sign up to set email alerts
|

Management of the first newborn delivered by a mother with COVID-19 in South Korea

Abstract: Clinical note Key message Question: How to manage the newborn born to the coronavirus disease 2019 (COVID-19) pregnant? Finding: Medical staff managed the delivery and neonatal care of a COVID-19 pregnant patient was based on the "Guidelines for COVID-19 response." Meaning: We desire that our management will help treat for subsequent patients and there should be updated continuously the prevention and control consensus strategies for newborn COVID-19. On March 6, 2020, a female neonate was born to a 28-yearold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Fifty-six studies were included in this review. Thirty one of the studies were conducted in China while the remaining studies were carried out in Iran (five) 1,14-17 , South Korea (two) 2, 18 , USA (seven) 3,[19][20][21][22][23][24] , Italy (four) [25][26][27][28] , Spain (three) [29][30][31] , Peru (one) 4 , France (one) 32 , Australia (one) 33 , Belgium (one) 34 (Table 1). All the studies were published between January and August 2020 (Table 1 Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-six studies were included in this review. Thirty one of the studies were conducted in China while the remaining studies were carried out in Iran (five) 1,14-17 , South Korea (two) 2, 18 , USA (seven) 3,[19][20][21][22][23][24] , Italy (four) [25][26][27][28] , Spain (three) [29][30][31] , Peru (one) 4 , France (one) 32 , Australia (one) 33 , Belgium (one) 34 (Table 1). All the studies were published between January and August 2020 (Table 1 Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A few studies documented the use of antiviral drugs like oseltamivir and acyclovir. 1,9,14,18 The effect of these drugs in the clinical course of COVID-19 infection is still being evaluated. In this review most of the neonates did not receive antiviral drugs and still had good outcome.…”
Section: Radiological Features Reported Include Bilateral Per-mentioning
confidence: 99%
“…Previous reports on newborns of mothers with COVID-19 in Korea reported about 4 infants born at full term via cesarean section and immediately separated from their mothers. 9 10 11 No infant tested positive for SARS-CoV-2. Our findings are consistent with those of previous case studies managed using a similar policy.…”
mentioning
confidence: 99%
“…
Early pandemic guidance was that mothers with COVID-19 should be separated from their babies immediately to avoid perinatal transmission. [1][2][3] However, emerging evidence has shown that placental, amniotic fluid and breast milk samples are usually virus-free. Newborn infections are uncommon, not severe and usually come from contact with infected carers or family.
…”
mentioning
confidence: 99%